CONVERSATION STYLES AND LANGUAGE FUNCTIONS USED BY THE MAIN CHARACTERS OF DONALD DUCK WALT DISNEY COMIC - Rulitasari, Juliana (Jurnal Ilmiah Mahasiswa FIB, 2013)
The writer analyzes conversation styles and language functions that are used by the main characters in Donald Duck Walt Disney comic who are Donald Duck and his nephews (Kwik, Kwek, and Kwak). Qualitative research method is used in this because the data analyzed are in the forms of words rather than numbers. The data source of this study is the English comic of Donald Duck published in 26thedition. The data for this study are taken from the utterances of the main characters in Donald Duck comic.  The study applies Yule’s theory about conversation styles and Cook’s about language functions. Based on the finding the conversation style often used are high involvement style and high considerateness style. Then, the main characters are used seven kinds of language functions. Those are emotive function, directive function, phatic function, poetic function, metalinguistic function, referential function, and contextual function.